2023
DOI: 10.1021/acssuschemeng.2c07103
|View full text |Cite
|
Sign up to set email alerts
|

Techno-Economic Analysis of Upgrading Corn Stover-Based Acetone, n-Butanol, and Ethanol to Higher Ketones and Alcohols: Fuels or Fine Chemicals?

Abstract: Acetone−butanol−ethanol (ABE) fermentation is a traditional industrial exploitation with a history of 100 years and the second largest fermentation industry in the world, second only to bioethanol fermentation. However, low ABE concentration in the fermentation broth, a complex separation process, and high separation cost are the bottlenecks of the biobutanol industry. Therefore, developing an efficient and energy-saving ABE upgrading process gives another approach to the reindustrialization of ABE fermentatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 71 publications
1
2
1
Order By: Relevance
“…Focusing on C11 selectivity, the statistical analysis suggested that C11 product formation increased by reducing C and increasing B , while there was no effect caused by the combination of the two. This is somehow contradictory to the trend observed by Xie et al, who found that an increase in Pd/C catalyst loading from 0.5 g/20 g ABE (2.5 wt %) to 1.5 g/20 g ABE (7.5 wt %) led to an increase in the product formation of higher ketones derived from alkylation. The authors noted, however, that increasing the catalyst loading to more than 10 wt % resulted in mass transfer problems during reaction, leading to lower results in terms of yield toward the formation of alkylation products.…”
Section: Resultscontrasting
confidence: 92%
See 3 more Smart Citations
“…Focusing on C11 selectivity, the statistical analysis suggested that C11 product formation increased by reducing C and increasing B , while there was no effect caused by the combination of the two. This is somehow contradictory to the trend observed by Xie et al, who found that an increase in Pd/C catalyst loading from 0.5 g/20 g ABE (2.5 wt %) to 1.5 g/20 g ABE (7.5 wt %) led to an increase in the product formation of higher ketones derived from alkylation. The authors noted, however, that increasing the catalyst loading to more than 10 wt % resulted in mass transfer problems during reaction, leading to lower results in terms of yield toward the formation of alkylation products.…”
Section: Resultscontrasting
confidence: 92%
“…No water was added as cosolvent in the present work, where the solvent was a reactant as well, thus making the final C higher than compared to the work by Xie et al Consequently, mass transfer limitations may also be the reason why higher activity (TON) was obtained in the present study with lower C . As for the B , the associated increase in double alkylation selectivity toward C11 was also seen in previous related studies, ,, as basicity promotes the alkylation to occur with the less reactive methyl group of the ketone . Moreover, as aldol condensation is base-catalyzed, higher B resulted in an increased overall alkylation efficiency.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations